2016
DOI: 10.3109/10428194.2016.1173210
|View full text |Cite
|
Sign up to set email alerts
|

Validation of cutaneous lymphoma international prognostic index (CLIPI) for mycosis fungoides and Sézary syndrome

Abstract: We sought to evaluate the performance of the cutaneous lymphoma international prognostic index (CLIPI), a prognostic index for mycosis fungoides (MF), and Sézary syndrome (SS), in our cohort of patients seen at Emory University between 1998 and 2013. Additionally, we examined the prognostic significance of lactate dehydrogenase (LDH), B0a/b, and CD30 status. A total of 390 patients were included in analysis: 78.2% early stage (IA-IIA), 7.2% with SS, 53.1% male, mean age 53.5 years. CLIPI stratified patients in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 22 publications
5
21
1
11
Order By: Relevance
“…Predictors of poor survival were advanced age, male sex, and stage >IB. Our study supports the previous literature, which suggests that advanced age and male sex are associated with poor survival [2,5,[13][14][15][16] . This is in keeping with the cutaneous lymphoma international prognostic index (CLIPi) for MF and SS, which lists male gender and age >60 as significant adverse prognostic factors [17] .…”
Section: Discussionsupporting
confidence: 82%
“…Predictors of poor survival were advanced age, male sex, and stage >IB. Our study supports the previous literature, which suggests that advanced age and male sex are associated with poor survival [2,5,[13][14][15][16] . This is in keeping with the cutaneous lymphoma international prognostic index (CLIPi) for MF and SS, which lists male gender and age >60 as significant adverse prognostic factors [17] .…”
Section: Discussionsupporting
confidence: 82%
“…The authors considered that the score had a good performance in terms of risk stratification for early stage MF patients, and as Benton et al, suggested its validation in appropriate prospective studies. 17 …”
Section: Discussionmentioning
confidence: 99%
“…With regard to serum LDH, it is known that this parameter has prognostic potential in CTCL. Several studies showed that elevated LDH is an indicator for worse outcome in CTCL patients . Unlike Dicer expression, however, Drosha expression has never been studied in the above‐mentioned context.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that elevated LDH is an indicator for worse outcome in CTCL patients. 3,15 Unlike Dicer expression, 9 however, Drosha expression has never been studied in the above-mentioned context. Gelmez et al 16 recently demonstrated that advanced-stage patients with chronic lymphocytic leukaemia showed decreased Dicer and Drosha expression.…”
Section: Discussionmentioning
confidence: 99%